Saikosaponin D Attenuates Pancreatic Injury Through Suppressing the Apoptosis of Acinar Cell via Modulation of the MAPK Signaling Pathway - Li, Caixia; Cui, Lihua; Zhang, Lanqiu; Yang, Lei; Zhuo, Yuzhen; Cui, Jialin; Cui, Naiqiang; Zhang, Shukun (Frontiers in Pharmacology, 2021)
Chronic pancreatitis (CP) is a progressive fibro-inflammatory syndrome. The damage of acinar cells is the main cause of inflammation and the activation of pancreatic stellate cells (PSCs), which can thereby possibly further aggravate the apoptosis of more acinar cells. Saikosaponind (SSd), a major active ingredient derived from Chinese medicinal herb bupleurum falcatum, which exerted multiple pharmacological effects. However, it is not clear whether SSd protects pancreatic injury of CP via regulating the apoptosis of pancreatic acinar cells. This study systematically investigated the effect of SSd on pancreatic injury of CP in vivo and in vitro. The results revealed that SSd attenuate pancreatic damage, decrease the apoptosis and suppress the phosphorylation level of MAPK family proteins (JNK1/2, ERK1/2 and p38 MAPK) significantly in the pancreas of CP rats. In addition, SSd markedly reduced the apoptosis and inflammation of pancreatic acinar AR42J cells induced by cerulein, a drug induced CP, or Conditioned Medium from PSCs (PSCs-CM) or the combination of PSCs-CM and cerulein. Moreover, SSd significantly inhibited the activated phosphorylation of JNK1/2, ERK1/2 and p38 MAPK induced by cerulein or the combination of PSCs-CM and cerulein in AR42J cells. Furthermore, SSd treatment markedly decreased the protein levels of p-JNK and p-p38 MAPK caused by PSCs-CM alone. In conclusion, SSd ameliorated pancreatic injury, suppressed AR42J inflammation and apoptosis induced by cerulein, interrupted the effect of PSCs-CM on AR42J cells inflammation and apoptosis, possibly through MAPK pathway.